2021
DOI: 10.1093/icesjms/fsab090
|View full text |Cite
|
Sign up to set email alerts
|

Epipelagic zooplankton diversity in the deep water region of the Gulf of Mexico: a metabarcoding survey

Abstract: Zooplankton is a key component in marine ecosystem health assessment. Here, we present a taxonomically comprehensive description of the zooplankton community (0–200 m) based on metabarcoding of the V9 hypervariable region of the 18S rRNA gene of 47 samples collected in the Gulf of Mexico (GoM) during summer 2015. Fourteen phyla were identified Arthropoda were dominant, with Calanidae, Metridinidae, and Euphausiidae as the most conspicuous families. Other abundant phyla were Cnidaria (Hydrozoa), Chordata (Tunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Moreover, metabarcoding abundances should be interpreted with caution, as the read patterns often do not correspond to the original proportions of species in the community (Günther et al, 2018;Piñol et al, 2015). However, we previously reported consistent abundance patterns between metabarcoding and morphological surveys for the oceanic waters of the GoM based on a detailed analysis of XIXIMI-4 (Martinez et al, 2021).…”
Section: Spatial and Temporal Variation Of The Zooplankton Communitymentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, metabarcoding abundances should be interpreted with caution, as the read patterns often do not correspond to the original proportions of species in the community (Günther et al, 2018;Piñol et al, 2015). However, we previously reported consistent abundance patterns between metabarcoding and morphological surveys for the oceanic waters of the GoM based on a detailed analysis of XIXIMI-4 (Martinez et al, 2021).…”
Section: Spatial and Temporal Variation Of The Zooplankton Communitymentioning
confidence: 87%
“…Studies on patterns of diversity and abundance of dominant taxa (e.g., copepods, euphausiids, salps, hyperiid amphipods) showed a relationship between species distribution and hydrological characteristics mostly imposed by prevailing mesoscale structures (Biggs et al, 1997; Castellanos & Gasca, 1999; Gasca, 2009; Hereu et al, 2020). Foregoing studies in this region showed a broad regional pattern in zooplankton assemblages partly explained by the environmental variables such as temperature, salinity and fluorescence (Hereu et al, 2020; Martinez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the northern GoM, the abundance of Syndiniales is positively correlated with copepod abundance, which are known hosts for this zooplankton group (Brannock et al, 2016). In addition, the Calanidae family was highly abundant in the water column during the oceanographic campaign XIXIMI-5 (Martinez et al, 2021). Despite their low abundance (Fig.…”
Section: Alveolata Dominates the ML And Dcmmentioning
confidence: 95%
“…Most of the studies performed on microbial eukaryotes in the Mexican Exclusive Economic Zone of the GoM (MEEZ) have focused on phytoplankton communities and employed microscopy analyses (Durán-Campos et al, 2017;Hernández-Becerril and Flores-Granados, 1998;Hernández-Becerril et al, 2008;Licea et al, 2016;Linacre et al, 2021;Merino-Virgilio et al, 2013;Okolodkov, 2003;Parra-Toriz et al, 2011); flow cytometry to detect Prochlorococcus, Synechococcus, heterotrophic bacteria, and picoeukaryotes (Linacre et al, 2019;2015); and molecular analyses, such as FISH-TSA, to detect picoeukaryotes like M. pusilla (Hernández-Becerril et al, 2012). In contrast, metabarcoding analyses are scarce and have focused on evaluating the bacterial composition of the water column (Raggi et al, 2020) and zooplankton communities (Martinez et al, 2021). Indeed, evaluations employing metabarcoding approaches to evaluate the entire protist community in the oceanic waters of the MEEZ have not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Grijalva-Usumacinta River System nitrogen X -24.4 ± 2.8 4.6± 0.6 models incorporate estimates of the variability in the isotope composition of the sources and trophic discrimination factors. The model inputs were (1) the d 15 N and d 13 C values of zooplankton, (2) the isotope ratios of suspended POM (mean and SD values, see Table 1) of the potential N sources for each region, and (3) the trophic discrimination factor for crustacean zooplankton of d 13 C = 1.0 ± 0.6‰, d 15 N= 2.0 ± 0.5‰ (Davenport and Bax, 2002;Vanderklift and Ponsard, 2003;Henschke et al, 2015); crustacean zooplankton are typically the dominant component of the community in the GM (Hopkins, 1982;Martinez et al, 2021). The model was applied to the zooplankton isotope ratios for all stations within each region.…”
Section: Sourcementioning
confidence: 99%